2006
DOI: 10.1099/vir.0.81067-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human papillomavirus type 16 oncoproteins on survivin gene expression

Abstract: Survivin has recently been identified as a novel member of the inhibitor of apoptosis (IAP) gene family. The product of this gene not only suppresses apoptosis but also controls cell division. Survivin is undetectable in most terminally differentiated normal tissues but is expressed in embryonic and fetal organs and is present in most malignant tumours. Human papillomaviruses (HPV) are thought to play an important role in the development of cervical cancer. By interfering in the cell cycle, the viral oncoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 30 publications
1
42
0
1
Order By: Relevance
“…Whether this release was dependent upon Bak remains to be evaluated. The E6 protein of the oncogenic cervical HPV 16 was reported to increase Survivin expression, and that this was dependent upon the ability of the E6 protein to promote p53 proteolysis [41], although no increase in Survivin expression was seen in HeLa cells that express HPV18 E6, an E6 type that is also capable of promoting p53 degradation, as compared to non-HPV-containing cells [39]. However, as the E6 protein of cutaneous HPVs cannot promote p53 degradation is seems unlikely that this mechanism contributes towards cell survival, although this awaits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this release was dependent upon Bak remains to be evaluated. The E6 protein of the oncogenic cervical HPV 16 was reported to increase Survivin expression, and that this was dependent upon the ability of the E6 protein to promote p53 proteolysis [41], although no increase in Survivin expression was seen in HeLa cells that express HPV18 E6, an E6 type that is also capable of promoting p53 degradation, as compared to non-HPV-containing cells [39]. However, as the E6 protein of cutaneous HPVs cannot promote p53 degradation is seems unlikely that this mechanism contributes towards cell survival, although this awaits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that high-risk HPV E6 proteins induce the proteosome-mediated degradation of p53 and that the expression of p53 results in downregulation of survivin promoter constructs. Therefore, it is suggested that the transactivation effect of HPV16 E6 on survivin appears to be mediated by the p53 degradation pathway (Mirza et al, 2002;Borbely et al, 2006).…”
mentioning
confidence: 99%
“…P53 supresses the expression of survivin, thus in conditions with loss of p53 function, such as cancer, expression of survivin is enhanced. HPV E6 induces the activity of survivin promoter region and increases endogenous survivin mRNA in human embryonic fibroblasts (Borbely, 2006;Mita, 2008) We propose a combined scoring system consisting of survivin expression by ICC and factors proved significant from multivariate analysis (Table 5). A biopsy will first be performed on the subject, classified to CIN 1, CIN 2, or CIN 3.…”
Section: Discussionmentioning
confidence: 99%